APLIKASI FIS MODEL SUGENO PADA PENGENDALIAN VALVE UNTUK MANGATUR TINGGI LEVEL AIR - Wahyudi Wahyudi; Iwan Setiawan; Martina Nainggolan (TEKNIK, 2007)
Fuzzy control is one of the controller alternative using expert system ( human being logic) as controller sothat do not need knowledge concerning parameter of systems. Fuzzy control also have ability of lightcomputing. This paper goal is making a Fuzzy control and observe the response of the plant had beencontrolled. The experiment’s purpose is to show the performance of Fuzzy control in control valve systemin order to liquid level controlling on-linely. Water level controlled by opening the load valve in the holdtank. The project experiment’s include examination conduct logic of Fuzzy program of Codevision AVR,examination of system at some references, examination the changing of liquid level reference, andexamination of system with the influence of disturbance. From the test, it is known that Fuzzy control withAVR ATmega8535 can yield eliminate offset in arranging opening of valve. Offset in examination ofsystem at some references are 0,4 cm , 0,02 cm , 0,17 cm, 0,11 cm, and 0,54 cm. Offset in examination thechanging of liquid levels are 0,07 cm, 0,02 cm, and 0,04 cm.